Achieving Public Policy Objectives Through Collective Agreements: The Project Agreement Model for Public Construction in British Columbia’s Transportation Sector - Calvert, John; Redlin, Blair (Just Labour, 2003)
The Construction of the 1.2 billion Vancouver Island Highway Project provided an opportunity for the building trades unions and the Government of BC to negotiate an innovative collective agreement that included union membership, training for local residents and members of equity groups, new employment opportunities for members of designated equity groups and a comprehensive health and safety program. The Project implemented the most comprehensive system of tracking progress in employment equity in BC’s history. By its completion, women, First Nations, persons with disabilities and visible minorities accounted for just under 20% of total hours worked in an industry where 2% representation is the norm. Over 94% of payroll went to local residents, ensuring their communities the benefits of this major capital project. Finally, the health and safety record was significantly better than on any comparable construction project. Far from being an impediment to the efficient and timely completion of this major construction project, the collective agreement made it possible to deliver training, employment opportunities and regional development